The Atrium in Atrial Fibrillation – A Clinical Review on How to Manage Atrial Fibrotic Substrates - Cunha, Pedro Silva (2022)
Funding Information: JH was supported by the “Netherlands Organization for Scientific Research NWO/ZonMWVidi 09150171910029”. PC, SL, and MO have not received any funding. Publisher Copyright: Copyright © 2022 Cunha, Laranjo, Heijman and Oliveira.